Odpowiedzi

2010-03-09T17:56:29+01:00
1) 2x=5x-7+1
2x-5x=-6
-3x=-6 /:(-3)
x=-2

2) 5x-3-3x=3-x
5x-3x+x=3+3
3x=6 /:(3)
x=2

3) -5(x-4)=2x-1
-5x+20=2x-1
-5x-2x=-1-20
-7x=-21 /:(-7)
x=3

4) (4x-1)+2(5-3x)=0
4x-1+10-6x=0
4x-6x=-10 +1
-2x=-9 /:(-2)
x=4½

5) (-5x-3)-(-x+8)=x
-5x-3+x-8=x
-5x-x+x=8+3
-5x=12 /:(-5)
x=-2 ⅖
2010-03-09T17:57:11+01:00
1)-3x=-6 /-3
x=2

2)3x=6/3
x=2

3)-5x+20=2x-1
-7x=-21/-7
x=3

4)4x-1+10-6x=0
-2x=-9/-2
x=4i1/2

5)-5x-3+x-8=x
-5x=11 /-5
x= -2 i 1/5
2010-03-09T17:59:57+01:00
1) 2x=5x-7+1
2x-5x=-6
-3x=-6 |:(-3)
x=2
2)5x-3-3x=3-x
5x-3x+x=3+3
3x=6 |:3
x=2
3)-5(x-4)=2x-1
-5x+20=2x-1
-5x-2x=-20-1
-7x=-21 |:(-7)
x=3
4)(4x-1)+2(5-3x)=0
4x-1+10-6x=0
4x-6x=1-10
-2x=-9 |(-2)
x=4,5
5)(-5x-3)-(-x+8)=x
-5x-3+x-8=x
-5x+x-x=3+8
-5x=11 |:(-5)
x=5,2